Advancements in Chemical Biology: Targeting Thyroid Gland Function and Disease through Novel Therapeutic Approaches - Abbas, Sumaya Fawzy Sabry; Lafta, Manar Basim Khalaf; Madlool, Zainab Khalid Obaid; Dhnieg, Marwa Rahim Matroud; Wahid, Mustafa Hussein Halool; Musleh, Mohammed Mazhar Hussein (American Journal of Biomedicine and Pharmacy, 2025)
The thyroid gland plays a crucial role in regulating metabolism, yet its dysfunction leads to various endocrine disorders, including hypothyroidism and hyperthyroidism. While traditional therapeutic approaches focus on hormone replacement and surgical interventions, emerging advancements in chemical biology offer novel strategies for targeted treatment. This study explores the application of molecular and cellular techniques in enhancing thyroid disease diagnosis and therapy. A qualitative review of recent chemical biology research and clinical trials was conducted, highlighting innovative approaches such as synthetic biological tools, protein-ligand interactions, and nanotechnology-based drug delivery. Findings reveal that these advancements improve treatment specificity, minimize side effects, and provide new avenues for personalized medicine. The results suggest that interdisciplinary collaboration and continued research into chemical biology methodologies can lead to more effective and less invasive treatments for thyroid disorders. This study emphasizes the need for integrating chemical biology innovations into standard thyroid disease management.